2008
DOI: 10.1002/per.676
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in school achievement: what are the roles of personality and achievement motivation?

Abstract: It is consistently reported that despite equal cognitive ability, girls outperform boys in school. In several methodological steps, the present study examined sex differences in school achievement and some of the most important personality and motivational constructs in a sample of 204 females and 138 adolescent males (mean age M = 16.94 years; SD = 0.71). Grades in Math and German as well as grade point average (GPA) served as achievement criteria. Intelligence, the Big Five of personality and motivational va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
123
4
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(160 citation statements)
references
References 73 publications
19
123
4
14
Order By: Relevance
“…These findings are different from those of Freudenthaler et al (2008), who found that school-related intrinsic motivation was more important to school achievement for boys than for girls. However, the findings from the present study are consistent with those of Ruban and McCoach (2005);Sánchez, Colón, and Esparza (2005); and Steinmayr and Spinath (2008). They did not find differences in the predictability of school performance and the relative importance of predictors across the two genders.…”
Section: Findings Relative To Previous Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are different from those of Freudenthaler et al (2008), who found that school-related intrinsic motivation was more important to school achievement for boys than for girls. However, the findings from the present study are consistent with those of Ruban and McCoach (2005);Sánchez, Colón, and Esparza (2005); and Steinmayr and Spinath (2008). They did not find differences in the predictability of school performance and the relative importance of predictors across the two genders.…”
Section: Findings Relative To Previous Studiessupporting
confidence: 82%
“…However, the findings of Freudenthaler et al (2008) were not conclusive, as other studies reported conflicting evidence. For instance, Steinmayr and Spinath (2008) did not find any gender difference in the relations between motivation and school achievement. Similarly, Ruban and McCoach (2005) found no gender differences in the impact of selfregulatory and motivation factors on college academic achievement.…”
Section: Gender Considerationsmentioning
confidence: 99%
“…Previous research has shown that goal orientations can predict academic achievement in children, adolescents and undergraduates, although the amount of variance explained by goals is small (Diseth, 2011;Elliot et al, 1999;Freudenthaler, Spinath, & Neubauer, 2008;Keys, Conley, Duncan, & Domina, 2012;Patrick, Ryan, & Pintrich, 1999;Simons, Dewitte, & Lens, 2004;Steinmayr, Bipp, & Spinath, 2011;Steinmayr & Spinath, 2008, 2009Wigfield & Cambria, 2010;Wolters, 2004;Huang, 2012). Independent of age, positive relations with academic achievement have been found for performance-approach goals (Daniels et al, 2008;Elliot et al, 1999;Wigfield & Cambria, 2010), and mastery goals (Bipp, Steinmayr, & Spinath, 2012;Daniels et al, 2008;Keys et al, 2012;Steinmayr et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Brojna istraživanja vezana za polne razlike u školskom uspjehu učenika, pokazala su da djevojčice nadmašuju dječake u školskom uspjehu i u većini školskih predmeta [5,[10][11][12]. Naše istraživanje je potvrdilo da pol učenika može biti izvor razlika u školskom uspjehu, tj.…”
Section: Diskusijaunclassified